Latihan Untuk Pasien Kanker Dengan Metastasis Tulang : Literature Review - Alvian Harisandy; Selamat Parmin; Serli Wulan Safitri (Universitas Muhammadiyah Klaten, 2024)
Preservation of physical function is the primary goal of cancer rehabilitation in patients with advanced cancer. The presence of bone metastases can lead to decreased physical function, decreased quality of life and fewer treatment options. The purpose of this study was to summarize and assess the safety and effectiveness of exercise in patients with bone metastases. The method used was a literature review through searching articles from several database journals used such as Google Scholar (Article Scholar). The results of a review of four articles related to exercise interventions in cancer patients such as exercise preserves physical function (aerobic, resistance, and flexibility exercises) supervised resistance training and unsupervised walking programs, unsupervised home-based exergaming can significantly improve physical function, strength, mental health, quality of life, fatigue. only one article was not very significant. Conclusion exercise in people with bone metastases, exercise appears to be safe and feasible, when it includes elements of supervised exercise instruction and is delivered by qualified exercise professionals.